Communities and cultural heritage
1 online resource.
Keywords: "Communities and Cultural Heritage explores the relationship between communities, their cultural heritage, and the global forces that control most of the world's wealth and resources in today's world. Bringing together scholars and heritage practitioners from nine countries, this book contributes to the ongoing dialogue on community heritage, by analysing impediments to full community participation. The undermining of local communities comes at a high price. As the chapters in this book demonstrate, the knowledge embedded within traditional and Indigenous heritage creates communities that are more resilient to environmental and social stressors and more responsive to contemporary challenges such as climate change, environmental degradation, post-disaster recovery and re-location. Cultural heritage practices often fail to capitalise upon local knowledge and traditional skills and undervalue the potential contribution of local communities in finding creative and resourceful solutions to the issues they are confronting. Arguing that the creation of successful community heritage projects requires ongoing reflection on the aims, methods, financing and acceptable outcomes of said projects, the volume also demonstrates that the decolonization of western-focused heritage practices is an ongoing process, by which subaltern groups are brought forward and given a space in the heritage narrative. Reflecting on trends that impact communities and heritage sites across different geographical regions, Communities and Cultural Heritage will be of interest to academics, students and practitioners of cultural heritage, archaeology and anthropology around the world"--